In Vitro Culture of The Natural Orchid Dendrobium spectabile (Blume) Miq. and The Characteristics of its Fragment 700 bp of the HOMEOBOX Homologous Gene - Ainina, Ana; Yudis Mahardhika, Ahmad; Rasjid, Nuzlan; Putu Ayu Erninda Oktaviani Suputri, Ni; Semiarti, Endang (Bogor Agricultural University, Indonesia, 2026)
D. spectabile is an orchid species endemic to Papua, which has the characteristic of sepals, petals, and a curly labellum, which is very attractive, so it needs to be preserved. Propagation of this plant with in vitro culture techniques promises plant propagation in large quantities and uniformly in a short time. In plants, the HOMEOBOX gene is recognized as a key regulator of gene transcription, playing a crucial role in plant organogenesis, particularly in the shoot apical meristem. This study aims to identify the optimal in vitro culture media for D. spectabile and to conduct molecular analysis of the HOMEOBOX gene. The methods used are: subculture, amplification, motif location analysis, physicochemical characterization, phylogenetic construction, and 2D protein sequence modeling. The results of the study showed that the subculture of D. spectabile on KC+IAA 20 µM media (20.67±1.76) significantly increased shoot growth. PCR with POH1 primer successfully amplified a 700 bp HOMEOBOX fragment containing 2 motifs: ELK, involved in protein-to-protein interactions, and Homeobox-KN, a transcriptional regulator. Phylogenetic analysis showed a close evolutionary relationship between D. spectabile and D. catenatum. Further studies are needed to obtain the complete sequence for functional validation in D. spectabile.